Current trends and advancements in the management of hepatocellular carcinoma - Teufel, Andreas; Kudo, Masatoshi; Qian, Yuquan; Daza Barragán, Jimmy Andres; Rodriguez, Isaac; Reißfelder, Christoph; Ridruejo, Ezequiel; Ebert, Matthias (Digestive diseases, 2024)
Background: Hepatocellular carcinoma (HCC) remains a significant global health burden with a high mortality rate. Over the past 40 years, significant progress has been achieved in the prevention and management of HCC. Summary: Hepatitis B vaccination programs, the development of direct acting antiviral drugs for Hepatitis C, and effective surveillance strategies provide a profound basis for the prevention of HCC. Advanced surgery and liver transplantation along with local ablation techniques potentially offer cure for the disease. Also, just recently, the introduction of immunotherapy opened a new chapter in systemic treatment. Finally, the introduction of the BCLC classification system for HCC, clearly defining patient groups and assigning reasonable treatment options, has standardized treatment and become the basis of almost all clinical trials for HCC. With this review, we provide a comprehensive overview of the evolving landscape of HCC management and also touch on current challenges. Key Message: A comprehensive and multidisciplinary approach is crucial for effective HCC management. Continued research and clinical trials are imperative to further enhance treatment options and will ultimately reduce the global burden of this devastating disease.
Online veröffentlicht: 7. Mai 2024
Gesehen am 19.08.2024